Penerapan Etika Bisnis Islam di Koppontren La Tansa Pondok Modern Darussalam Gontor, Tahun 2015 - Nugraha, Ahmad Lukman (FALAH Jurnal Ekonomi Syariah, 2016)
Discussion in ethics of business activity poped out to minimize cheating and fraud. But actually, business ethics felt difficult to apply in practice. Modern Islamic Boarding School Darussalam Gontor as one of the self-help Islamic Boarding Schools supported by cooperatives in pesantren (koppontren) in their activities. This paper aims to understand the application of Islamic buseness ethic in Koppontren La-Tansa Gontor. This research uses mix method which is sequential explanatory design and case study, questionnaires, interviews, observation and documentation used to collecting data in this research. Data analysis was performed through data reduction, data display, and data verification. The results of this research can be explained as: first, La-Tansa cooperatives sector Gontor can run the business activities with the implementation of business ethics according to the Qurâan and Sunnah values. Appear from the height understanding of the business to the axiom business ethics and the height application in business activities in each business sector. Second, the character of kyai and business unit supervisor are high. According to the data, showed that a level of the heigh direction is 80 persent and control on the application of business ethics is 72 percent. Thus, the Islamic buseness ethic can be applied on firmâs and govermentâs law with height understanding and controlling.